Strategi Guru Community Learning Center untuk Menumbuhkan Cinta Tanah Air pada Anak Pekerja Migran Indonesia di Sarawak-Malaysia - Khamdah, Nur; Awaliyah, Siti; Wiyono, Suko (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
The purpose of this study is to analyze the strategies, obstacles, and solutions implemented by teachers at Community Learning Centers in fostering a spirit of patriotism among the children of Indonesian migrant workers. This study used a descriptive qualitative approach with observation, interviews, and document study techniques. The strategies of Community Learning Center teachers in fostering a spirit of patriotism in Indonesian migrant workers' children are realized through internal activities, extracurricular activities, and external activities. Internal activities are carried out in the form of formal learning, flag ceremonies, morning assemblies, morning routines, and independence day celebrations. Extracurricular activities include entrepreneurship, dance, angklung musical instrument training, and music groups. External activities include jamborees, olympiads, arts and sports weeks, cultural festivals, competitions in commemoration of heroes' day, and activities carried out to support the continuity of education for migrant workers' children in Indonesia. The obstacles faced are an insufficient number of teachers, limited time, low awareness among parents, diverse language use, difficult internet access, lack of facilities and infrastructure, suboptimal budget allocation, and low interest among students to continue their education in Indonesia. Efforts made include optimizing the management of teachers' tasks and responsibilities, conducting home visits and pollen activities, promoting the use of Indonesian language, requesting the provision of facilities, implementing cross-subsidies, and requesting the issuance of cross-border travel documents from the Consulate General of the Republic of Indonesia.